Vertically nanotwinned TiO2 photoanodes with enhanced charge transport for efficient solar water splitting. (September 2020) - Lu, Yang; Chiang, Ching-Yu; Huang, Eugene
Highlights: The vertically nanotwinned TiO2 films on FTO substrates are synthesized by a novel strategy for the first time. The crystal orientation of nanotwins and the tilts of twin boundaries are quantitatively visualized by the scanning synchrotron X-ray Laue nanodiffraction. The twin-induced "highway-like" transport channels vertically aligned on the substrate boost the charge carriers transport and solar water splitting. Abstract: Nanotwinned crystals are highly desired for materials science and practical applications due to their various intriguing properties. In particular, a semiconducting photoanode with vertically aligned twin boundaries could simultaneously possess excellent charge separation and transport properties, but the synthesis remains a great challenge. Here, we report highly oriented rutile TiO2 nanotwin crystals grown on conducting substrates via a rapid hydrothermal method for the first time. The scanning synchrotron X-ray Laue nanodiffraction demonstrated that the twin boundaries in the film are strikingly perpendicular to the plane of the substrate. The nanotwin photoanode exhibited superior photoelectrochemical water oxidation activity mainly due to the massive improvement in the electrical transport. This work offers exciting opportunities for designing and fabricating new classes of ordered nanotwins. Graphical abstract: The vertical nanotwin TiO2 photoanodes are prepared by a rapid hydrothermal strategy to simultaneously promote the separation and transport of photo-excited charge carriers. The twin-induced highway-like charge transport system leads to a significant improvement of performance towards solar-driven water splitting. Image, graphical abstract